2018
DOI: 10.1016/j.jmb.2018.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Polarity Protein Levels in the Developing Central Nervous System

Abstract: In the course of their development from neuroepithelial cells to mature neurons, neuronal progenitors proliferate, delaminate, differentiate, migrate, and extend processes to form a complex neuronal network. In addition to supporting the morphology of the neuroepithelium and radial glia, polarity proteins contribute to the remodeling of processes and support the architectural reorganizations that result in axon extension and dendrite formation. While a good amount of evidence highlights a rheostat-like regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The field had focused on post-translational rheostat-like polarity signaling mechanisms based on polarity protein phosphorylation and asymmetric subcellular partitioning of signaling complexes (McCaffrey and Macara, 2009;Namba et al, 2015). Recent vertebrates studies revealed diverse polarity regulatory mechanisms, including global switch-like mechanisms whereby polarity competency is modulated through expression levels of polarity genes as in polarity inhibition by microRNAs, ubiquitin ligases (Cheng et al, 2011;Famulski et al, 2010;Laumonnerie and Solecki, 2018), and now Hif1a-Zeb1-mediated transcriptional repression. Unexpectedly, Hif1a regulation of Pard-complex function via Zeb1 is the first known example of cellular polarity modulation by O 2 tension during development, in the nervous system or elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field had focused on post-translational rheostat-like polarity signaling mechanisms based on polarity protein phosphorylation and asymmetric subcellular partitioning of signaling complexes (McCaffrey and Macara, 2009;Namba et al, 2015). Recent vertebrates studies revealed diverse polarity regulatory mechanisms, including global switch-like mechanisms whereby polarity competency is modulated through expression levels of polarity genes as in polarity inhibition by microRNAs, ubiquitin ligases (Cheng et al, 2011;Famulski et al, 2010;Laumonnerie and Solecki, 2018), and now Hif1a-Zeb1-mediated transcriptional repression. Unexpectedly, Hif1a regulation of Pard-complex function via Zeb1 is the first known example of cellular polarity modulation by O 2 tension during development, in the nervous system or elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…For example, parallel transcriptional (e.g., Zeb1 [Singh et al, 2016]) and ubiquitination (e.g., Siah2 [Famulski et al, 2010]) pathways act in a switch-like manner linking polarity to neuronal differentiation and migration initiation by controlling the onset of partitioning-defective (Pard)-complex gene or protein expression. Despite advances in our knowledge of these cell-intrinsic mechanisms endowing differentiating neurons with new polarity-dependent cell biological activities (Singh and Solecki, 2015;Laumonnerie and Solecki, 2018;Uzquiano et al, 2018), key challenges remain to our understanding of how polarity signaling is affected by dynamic cell-extrinsic environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the specific regions of a neuron where growth cones form is an important problem; neuronal polarity is key to the formation of the axon (a single output process) and dendrites (multiple input processes; Laumonnerie and Solecki, 2018 ). Neuronal polarity determination has been classified into five stages (Dotti et al, 1988 ), namely, stage 1: initiation of the emergence of the minor process(es); stage 2: the growth of the minor processes; stage 3: axon specification; stage 4: dendritic specification; and stage 5: synaptogenesis.…”
Section: Neuronal Polarization and The Need For Its Rapid Determinatimentioning
confidence: 99%
“…Analogously, in neurons, where cell polarity is also crucial, the localization of the proteasome targets the degradation of ubiquitylated proteins, required for axon development (Otero et al, 2014;Hsu et al, 2015) and presynaptic differentiation (Pinto et al, 2016;Liu et al, 2019). Here, a polarized phenotype is achieved by the selective degradation of polarity proteins, such as PAR-2, PAR-3, PAR-6 (Laumonnerie and Solecki, 2018), and actin polymerizing factors, such as VASP by the UPS (Boyer et al, 2020). Interestingly, upon activation, B cells upregulate the ubiquitylation of proteins, including BCR downstream signaling molecules, polarity proteins, and actin polymerizing factors (Satpathy et al, 2015), highlighting a role for the UPS in regulating actin dynamics and B cell activation.…”
Section: Introductionmentioning
confidence: 99%